Development of a mechanistic model of leaf surface gas exchange coupling mass and energy balances for life-support systems applications. (October 2020) - Poulet, Lucie; Dussap, Claude-Gilles; Fontaine, Jean-Pierre
Abstract: Growing plants in space during long-duration missions will be crucial to ensure functions such as food production, air revitalization, and water purification, and requires an in-depth understanding of plant growth and development processes in reduced gravity. In particular, gas exchange at the leaf surface is considerably reduced because of lack or reduction of buoyancy-driven convection, which can translate into reduced biomass production in the long run. To quantify this impaired gas exchange and biomass production, this study formulates a mechanistic model of these variables in low gravity following a chemical engineering approach. The emphasis here is set on short-term physical response of gas exchange at the leaf surface to gravity and airspeed. A mass balance with stoichiometric limitations enables the computation of mass exchange fluxes, and an energy balance relates them to heat transfer fluxes. Leaf surface temperature and biomass production in the form of dry mass and free water mass are then subsequently computed. The validation of this model on sets of independent data from published parabolic flight experiments is presented and a sensitivity study to different parameters highlights the existence of threshold values for gravity, ventilation, light, and stomatal conductance, which dictate the magnitude of changes in leaf surface temperature and photosynthesis rate. These results show that a mechanistic modeling approach coupled to a dedicated experimental approach are key to identify adequate growth conditions for plants in reduced gravity environments. Abstract : A leaf gas exchange model with gravity as input is validated on independent datasets. Reducing gravity below a critical threshold leads to reduced gas exchange at low air speeds. Well-watered plants are more sensitive to gravity changes than plants under water stress. Leaf shape strongly affects leaf temperature in low gravity regardless of airspeed. Coupled mechanistic model and dedicated experiments are key for space plant growth.